2013
DOI: 10.2166/wst.2013.019
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic parasites and enteroviruses in wastewater: support for a regulation on water reuse

Abstract: Brazilian regulations for nonpotable reuse are being established using World Health Organization guidelines, however, they should be developed based on local monitoring studies. This study intended to analyze enteroviruses, protozoa and viable Ascaris sp. eggs in raw (24) and treated (24) effluents from four Wastewater Treatment Plants of São Paulo State, Brazil. The protozoa were detected with the US Environmental Protection Agency (USEPA) Method 1623 in the treated effluents and by centrifugation/Immunomagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 11 publications
0
11
0
4
Order By: Relevance
“…With the population increase and urbanization, biosolid production also has increased and the application of this residue to soil for fertilization purpose represents the best option for disposal as this is rich in nutrients (Guadagnini et al 2013;Hachich et al 2013;Lima et al 2012;Lu et al 2012;Silva et al 2012). However, inherent in its use in agriculture are concerns about its effects on public health due to uncertainties surrounding the presence of enteric parasites, which can be sources of contamination in both food and surface water and groundwater; the low infective dose of certain pathogens, especially Cryptosporidium and Giardia; the possible growth of pathogenic bacteria, such as coliforms, which are used as indicators of safety but do not predict the presence of other pathogens (Abreu-Acosta and Vera 2011); and the potential for diseases caused by unknown agents (Santamaria andToranzos 2003, Sidhu andToze 2009).…”
Section: Introductionmentioning
confidence: 99%
“…With the population increase and urbanization, biosolid production also has increased and the application of this residue to soil for fertilization purpose represents the best option for disposal as this is rich in nutrients (Guadagnini et al 2013;Hachich et al 2013;Lima et al 2012;Lu et al 2012;Silva et al 2012). However, inherent in its use in agriculture are concerns about its effects on public health due to uncertainties surrounding the presence of enteric parasites, which can be sources of contamination in both food and surface water and groundwater; the low infective dose of certain pathogens, especially Cryptosporidium and Giardia; the possible growth of pathogenic bacteria, such as coliforms, which are used as indicators of safety but do not predict the presence of other pathogens (Abreu-Acosta and Vera 2011); and the potential for diseases caused by unknown agents (Santamaria andToranzos 2003, Sidhu andToze 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Norway (Robertson et al, 2006) and Spain (Castro-Hermida et al, 2010), high numbers of cysts were found in raw sewage influent samples that contained from 10 2 to 1.36x10 4 cysts/L and 2 to 1.44x10 4 cysts/L. In Brazil, cysts were detected at concentrations as high as 10 5 cyst/L (Neto et al, 2006;Hachich et al, 2013). In contrast, relatively few studies have reported cysts at concentrations not exceeding 100 cysts/L (Reinoso et al, 2011;Yapo et al, 2014;Zhang et al, 2015).…”
Section: Raw Sewage and Sludgementioning
confidence: 97%
“…High prevalence rates of Giardia in raw wastewater were reported in both developed and developing countries. Surveys undertaken in North America (Harwood et al, 2005;Kitajima et al, 2014), Europe (Cacciò et al, 2003;Reinoso et al, 2011;Rodriguez-Manzano et al, 2012), Asia (Oda et al, 2005;Lim et al, 2007;Ma et al, 2016) and South America (Hachich et al, 2013) reported the presence of cysts in up to 100% of the raw sewage influent samples tested. The number of cysts /L of raw sewage was found to vary from hundreds to thousands.…”
Section: Raw Sewage and Sludgementioning
confidence: 99%
“…Cryptosporidium é desenvolvida em centros de pesquisas (FRANCO et al, 2001;SANTOS et al, 2004;HACHICH et al, 2004;MACHADO et al, 2009;RAZZOLINI et al, 2010; ARAUJO et al, 2011;HACHICH et al, 2013; BONATI & FRANCO, 2014). Entretanto, a detecção de Cryptosporidium em amostras de águas continua sendo um desafio, sobretudo no Brasil, devido à inexistência de dados epidemiológicos de surtos de criptosporidiose, e à dificuldade de implementação e otimização de métodos de detecção e quantificação acessíveis, em termos de custos, e reprodutíveis quando aplicados nas águas dos manaciais do nosso país (ARAUJO et al, 2011).…”
Section: Em Amostras Ambientais Grande Parte Das Pesquisas De Detecçãunclassified
“…Cryptosporidium é desenvolvida em centros de pesquisas (FRANCO et al, 2001;SANTOS et al, 2004;HACHICH et al, 2004;MACHADO et al, 2009;RAZZOLINI et al, 2010;ARAUJO et al, 2011;HACHICH et al, 2013;BONATI & FRANCO, 2014 ou sequenciamento do fragmento para estudo de posicionamento taxonômico dos organismos a fim de melhorar a efetividade na investigação e aperfeiçoar o processo, tornando-o mais rápido (HIGGINS et al, 2003;ZHOU et al, 2003;XIAO et al, 2004;RYAN et al, 2005;ARAUJO, 2008;PLUTZER e TOMOR, 2009 MEYER et al, 2010).…”
Section: Em Amostras Ambientais Grande Parte Das Pesquisas De Detecçãunclassified